2022
DOI: 10.1101/2022.01.20.476184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ECS1 and ECS2 regulate polyspermy and suppress the formation of haploid plants by promoting double fertilization

Abstract: In flowering plants, the number of pollen tubes that provide sperm cells to the female gametes is restricted by a pollen tube block. This safeguard mechanism is only activated after successful fertilization of both female gametes and involves the disintegration of pollen tube attracting synergid cells. Yu and coworkers previously reported that the endopeptidase ECS1 and ECS2, which are secreted by fertilized egg cells, prevent the attraction of supernumerary pollen tubes by cleaving the pollen tube attractant … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…It also represents a novel seed‐based system to induce haploid plants in dicots. A similar haploid inducer line acting from the female side was very recently reported including one preprint (Mao et al ., 2022; Zhang et al ., 2023). In this case, these are mutations of two egg cell‐specific aspartic endopeptidases (ECS1 and ECS2) that trigger maternal haploid induction (Zhang et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also represents a novel seed‐based system to induce haploid plants in dicots. A similar haploid inducer line acting from the female side was very recently reported including one preprint (Mao et al ., 2022; Zhang et al ., 2023). In this case, these are mutations of two egg cell‐specific aspartic endopeptidases (ECS1 and ECS2) that trigger maternal haploid induction (Zhang et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report the first female in planta haploid‐inducing system by mutation of a phospholipase A family of gene in Arabidopsis . One case of female‐based in vivo haploid induction system has recently reported (Mao et al ., 2022; Zhang et al ., 2023), but the mutagenized target genes encode egg cell‐specific peptidases, which indicates the underline mechanism can be different.…”
Section: Introductionmentioning
confidence: 99%
“…Atecs1/2 presents a defective egg cell/sperm cell attachment phenotype, impairing preferential egg cell fertilization (J. . Accordingly, Mao et al (2023) suggested that HI in Atecs1/2 is related to the function of AtECS1/2 in gamete fusion and double fertilization coordination, although other mechanisms in ECSmediated HI cannot yet be discounted.…”
Section: Egg Cell Fertilization-dependent Haploid Inductionmentioning
confidence: 99%
“…EGG CELL-SPECIFIC1/2 ( ECS1 /2) encodes egg cell-specifically expressed aspartic proteases, which are secreted to the synergid cell region upon fertilization to avoid polytubey by degrading the pollen tube attractant LURE1 [ 75 ]. Recently, two independent studies demonstrated that the mutation of ECS1 and ECS2 can also induce haploid embryogenesis [ 76 , 77 ]. Unfused sperm nuclei were observed in zygotes and early embryos, suggesting that karyogamy defects occurred in the sperm–egg fertilization, and the haploids from the ecs1 ecs2 mutant progenies may have resulted from the post-fertilization genomic elimination [ 77 ].…”
Section: Parental Factor-mediated Haploid Embryogenesismentioning
confidence: 99%